The Effect of Land Cover Changes on Water Quality in the Cisadane River Basin, West Java, Indonesia - Hidayat, Harry; Effendi, Hefni; Budi Prasetyo, Lilik (LIMNOTEK Perairan Darat Tropis di Indonesia, 2025)
The availability of water and quality of clean water are increasingly affected by population growth. As the human population expand, the demand for goods and services rises, often leading to intensified in water use and pollution. This study examines the correlation between land cover changes and water quality in the Cisadane River Basin. Water quality data were collected as a time series from 2019 to 2022, focusing on eight parameters:  TDS, TSS, BOD5, COD, DO, TP, NO3-N, and NH3-N. Water quality classification was carried out using the Pollution Index (IP) method. Land cover changes were analyzed through visual interpretation using ArcGIS at a 1:10,000 scale. Multiple linear regression analysis was used to assess the influence of land cover on river water quality. The results indicate that the overall water quality in the Cisadane River Basin falls under the ‘slightly polluted’ category, with noticeable influence from land cover changes. Between 2019 and 2022, built-up land increased by approximately 5.5% contributing to elevated BOD₅ levels in several locations, such as Babakan and Genteng, indicating rising organic pollution from domestic waste and urban activities. Conversely, a decrease in vegetation cover by around 6.3% at various observation points correlated with decreased DO levels, especially in downstream areas such as Tanjung Burung and Vihara, potentially disrupting aquatic ecosystem balance. These findings suggests that vegetation cover plays an important role in maintaining water quality and ecological stability, while the expansion of built-up and agricultural areas tends to elevate pollutant loads in river water. Therefore, the results of this study can serve as a reference for policymakers in spatial planning of the Cisadane River Basin, especially in developing land conservation and waste management strategies to improve water quality and maintain the sustainability of water resources in the region